Implementation of Storyboarding and Compositing in the 2D Animation “Spectrum Rise” - Yuliendri, Afandra; Fris Okta Falma (The Future of Education Journal, 2025)
This final project report discusses the process of designing the storyboard and compositing in the production of a 2D animation titled “Spectrum Rise.” The animation aims to convey the importance of literacy through an engaging visual approach. The development method employed is a pipeline, which includes pre-production, production, and post-production stages to ensure an efficient and structured workflow. In the storyboard design phase, thumbnail sketching techniques are applied to quickly and effectively explore visual ideas. In the compositing stage, layering techniques are used to assemble visual elements into a cohesive frame. This process is supported by the use of Clip Studio Paint for storyboarding and Adobe After Effects for compositing. The final outcome demonstrates that the applied methods and techniques successfully result in a communicative storyboard and compositing that effectively enhances the atmosphere and emotion of the story. This report is expected to serve as a reference for practitioners and students in the field of animation, particularly in the visual design stage.